The Effect of Brand Trust on Repurchase Intention Through Brand Love as a Mediating Variable (Study on Thrift Shopping Customers with the Uniqlo Brand) - Fadlilah, Ahmad; Widyastuti, (Proceeding of International Management Conference and Progressive Papers, 2023)
Repurchase intention is a buying activity that is carried out repeatedly. Repurchase intention will arise if the product purchased meets consumer expectations. Repurchase intention can be formed if brand trust and brand love have been fulfilled in the brand. This study aims to analyze the effect of brand trust on repurchase intention through brand love as a mediating variable in studies on thrift shopping customers with the Uniqlo brand. This research is a quantitative study with a sampling technique through purposive sampling on 210 respondents. Questionnaires were distributed directly to 210 respondents by measuring the answers using a Likert scale. The data analysis technique used is path analysis using the AMOS program. The results of the study show that brand trust has a positive effect on brand love. Furthermore, brand love affects repurchase intention and brand trust has a positive effect on repurchase intention.